STUDI AL-QUR’AN DAN HADIS ATURAN HUKUM KONKRIT: IJARAH (SEWA MENYEWA) - Dhaifina Fitriani (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
Islamic shariah allows rent contracts to fulfill human needs, but the actities is bound bt the contract. A lease agreement is called Ijarah which means a lease agreement mad by the lessee and the holder of an item within a certain time through lease payment. Whereas Ujrah is a tenancy agreement made by the tenant and the service holder for the services needed within a certain time through lease payment. The risk of objects in lease agreement is borne by the holder (the renter) because the tenant just has the power to take advantage of the leased goods. The lease agreement will end when there’s a disgrace on the rental goods, damage to the rental goods, fulfilled by the acquired benefits and due to aging. This paper aims to inform the reader about the concrete laws contained in the Ijarah contract (leases). The author uses analysis studies (analysis studies) by collecting primary data and secondary data from library research (library research) and using a juridical normative approach in analyzing data.